Combined radioprotection by preirradiation peroral cystamine and postirradiation glucan administration - Pospísil, M; Netíková, J; Pipalová, I; Jarý, J (Folia biologica, 1991)
The possibilities of combined radioprotection, using preirradiation peroral cystamine and postirradiation intraperitoneal glucan administration in sublethally and lethally whole-body gamma-irradiated mice were investigated. The results demonstrated at least additive radioprotective effects of both agents, manifested in the enhancement of postirradiation haemopoietic recovery and increased survival of irradiated mice. The effects appear to depend on the sequential cell protection mediated by cystamine and enhanced haemopoietic repopulation induced by glucan.
Keywords: kostní dřeň; Radiation-Protective Agents; Femur; Spleen; slezina; záření gama; Cystamine; beta-glukosidasa; Gamma Rays; celotělové ozáření; Hematopoietic Stem Cells; cystamin; Hematopoiesis; lékové interakce; myši; Glucan 1,3-beta-Glucosidase; Drug Interactions; Mice; beta-Glucosidase; Bone Marrow; glukan-1,3-beta-glukosidasa; hematopoéza; mužské pohlaví; zvířata; Animals; radioprotektivní látky; Male; hematopoetické kmenové buňky; Whole-Body Irradiation; tolerance záření; Radiation Tolerance; femur